THE ROLE OF KITAB LUBAB AL-HADIST IN ENHANCING OF DHIKR AMONG MAJELIS TA'LIM AL-WUSTHO CONGREGATION - Soraya, Syarifah; Rahmawati, Nadiyah (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2025)
Dhikr mentioning and remembering Allah is not only commanded by Allah and His Messenger, but will also bring direct benefits to everyone who is dhikr. Whoever the person is and under any conditions, dhikr will have a positive impact. Dhikr will give peace to the public just like what a kiyai and ustadz enjoy. Dhikr will soothe a hard man's heart just as it soothes a gentle woman's heart. When people dhikr, God will be close to them without limits and status. However, many ta'lim assembly worshippers are not motivated to dhikr. It is often found that there is a lack of understanding of the congregation for the concept of dhikr in depth. This causes the dhikr to be less meaningful and does not have a significant impact on their spiritual life.This research aims to determine the role of the Book of Lubab Al-Hadith in improving the understanding, motivation, and quality of dhikr of the Ta'lim Al-Wustho Assembly. The research method used is qualitative with a phenomenological approach. Data collection techniques are carried out through in-depth interviews, participant observations, and documentation. The data obtained was analyzed using the Miles and Huberman model. The results of the study show that the Book of Lubab Al-Hadith has an important role in increasing the understanding and motivation of the Ta'lim Al-Wustho Assembly congregation in dhikr. The congregation's understanding of dhikr has become deeper, their motivation to dhikr has increased, and the quality of their dhikr has improved. This has a positive impact on the spiritual life of the congregation, which can be seen from the increase in peace of mind, closeness to Allah SWT, and enthusiasm in worship. This research makes a significant contribution in understanding the role of the book of hadith in improving the practice of dhikr and spirituality of Muslims. The findings of this study can be used as a reference for ustadz, ta'lim council administrators, and researchers in developing a more effective dhikr coaching program.